Pro Oracle Database 11g RAC on Linux - Shaw, Steve; Bach, Martin; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Pro Oracle Database 11g RAC on Linux provides full-life-cycle guidance on implementing Oracle Real Application Clusters in a Linux environment. Real Application Clusters, commonly abbreviated as RAC, is Oracle$1 (Bs industry-leading architecture for scalable and fault-tolerant databases. RAC allows you to scale up and down by simply adding and subtracting inexpensive Linux servers. Redundancy provided by those multiple, inexpensive servers is the basis for the failover and other fault-tolerance features that RAC provides. Written by authors well-known for their talent with RAC, Pro Oracle Database 11g RAC on Linux gives you a rock-solid and technically flawless foundation on which to build your RAC-management skills. Authors Julian Dyke and Steve Shaw share their hard-won experience in building RAC clusters, showing you how to build for success using the very latest Oracle technologies, such as Automatic Storage Management (ASM) and Oracle Clusterware. You$1 (Bll learn to troubleshoot performance and other problems. You$1 (Bll even learn how to correctly deploy RAC in a virtual-machine environment based upon Oracle VM, which is the only virtualization solution supported by Oracle Corporation. RAC is a complex and powerful technology. It demands expertise in its deployment. You can$1 (Bt just (3z(Bwing it(3y (Bin creating a RAC solution. Julian and Steve have earned the right to term themselves expert$1 (Bin Pro Oracle Database 11g RAC on Linux, they offer a rigorous and technically-correct treatment of RAC that helps you build a solid foundation of expertise and achieve success. Rigorous and technically accurate content Complete coverage of RAC, from planning to implementation to rollout to ongoing maintenance and troubleshooting Up-to-date with the very latest RAC featuress
RAC Concepts -- RAC Architecture -- Hardware -- Virtualization -- Linux Installation and Configuration -- Grid Infrastructure Installation -- Clusterware -- Automatic Storage Management -- RDBMS Installation and Configuration -- Workload Management -- Oracle Performance Monitoring -- Linux Performance Monitoring -- Parallel Execution -- Upgrading to Oracle 11g Release 2.
Keywords: Computer science; Database management; Computer Science; Database Management